2007
DOI: 10.1037/0096-3445.136.4.623
|View full text |Cite
|
Sign up to set email alerts
|

Low target prevalence is a stubborn source of errors in visual search tasks.

Abstract: In visual search tasks, observers look for targets in displays containing distractors. Likelihood that targets will be missed varies with target prevalence, the frequency with which targets are presented across trials. Miss error rates are much higher at low target prevalence (1-2%) than at high prevalence (50%). Unfortunately, low prevalence is characteristic of important search tasks like airport security and medical screening where miss errors are dangerous. A series of experiments show this prevalence effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

58
546
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(611 citation statements)
references
References 45 publications
58
546
7
Order By: Relevance
“…So far, the visual search and categorisation literature are rarely brought together (cf. Smith et al, 2005;Wolfe et al, 2007) because categorisation often requires identifying targets presented in isolation, whereas visual search requires discriminating targets from simultaneously presented distractors. Presumably, if training variability improved the visual differentiation of targets within cluttered bags, a possibility is that the benefit of training variability would disappear in the absence of cluttered images.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the visual search and categorisation literature are rarely brought together (cf. Smith et al, 2005;Wolfe et al, 2007) because categorisation often requires identifying targets presented in isolation, whereas visual search requires discriminating targets from simultaneously presented distractors. Presumably, if training variability improved the visual differentiation of targets within cluttered bags, a possibility is that the benefit of training variability would disappear in the absence of cluttered images.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has responded by increasing the diversity of stimuli and expanding the variety of contexts in which cognition is studied. For example, depicted eyes and human limbs have replaced symbolic arrows in studies of attentional orienting (Nummenmaa & Calder, 2009); photos and video clips have replaced line drawings in studies of face and scene perception (Henderson, 2005;Palermo & Rhodes, 2007); and airport security and mammography xrays have replaced geometric shapes in studies of visual search (Wolfe, Horowitz, Van Wert, Kenner, & Kibbi, 2007;Wolfe & Van Wert, 2010). Although we see these trends as increasing the naturalism of cognitive research at the level of inputs and settings, we note that there has been less progress made in the measurement of the mind's output, as expressed in behavior.…”
mentioning
confidence: 99%
“…Chen, Meier, Blair, Watson, & Wood, 2013). One further possibility stands out: the role of expectations regarding the likelihood of threat being present Godwin, Menneer, Cave, Helman, et al, 2010;Van Wert, Horowitz, & Wolfe, 2009;Wolfe & Van Wert, 2010;Wolfe et al, 2007;Wolfe, Horowitz, & Kenner, 2005). Previous studies examining the prevalence effect in visual search have found that, when targets are presented on a high proportion of trials (>50% of trials), then participants show a tendency to spend longer times searching, as well as a tendency to report that they believe targets to be present.…”
Section: Discussionmentioning
confidence: 99%